Ladies of liberty : [compact disc, abridged] : the women who shaped our nation - Roberts, Cokie (Harper Audio, 2008)
Shares the stories of remarkable women who shaped American history between 1796 and 1828, including Dolley Madison, Theodosia Burr, and Sacajawea.